«Բազմավէպը» ՝ հայկական հնագույն հանդես - Կարապետյան, Արմեն (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Одним из важнейших периодических изданий Конгрегации мхитаристов был журнал «Базмавеп», первый номер которого вышел в 1843 г. в Венеции. Примечательно, что «Базмавеп» издается по сей день. One of the most significant periodicals of the Mekhitarist Congregation was the journal “ Bazmavep” . The first issue of the journal was published in 1843, in Venice. It is noteworthy that the journal is still being published.
Keywords: Պատմություն; Հայ մամուլ